Gravity Mapping in Canada: A Review of Progress - Thomas, M.; Gibb, R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1977)
Summary We review progress made in the gravity survey of Canada from its inception in the early part of this century to the present time. We briefly describe the National Gravity Network of control stations and its relationship to the International Gravity Standardization Net of 1971. Gravity data services offered to the private and public sectors by the Gravity and Geodynamics Division of Earth Physics Branch are also described briefly.